Solid polymer electrolytes based on chitosan and europium triflate - Alves, Raquel Diana Carneiro (2016)
Solid polymer electrolytes (SPEs) were obtained from chitosan plasticized with glycerol and contained europium (III) trifluoromethanesulfonate salt. The transparent samples were characterized by thermal analysis (DSC and TGA), impedance spectroscopy and electron paramagnetic resonance (EPR). The sample with 55.34 wt.% of europium triflate showed the best ionic conductivity of 1.52 × 10−6 and 7.66 × 10−5 S cm−1 at 30°C and 80°C, respectively. The thermal analysis revealed that the degradation started at around 130–145°C and the weight loss ranged from 20 to 40%. The DSC of the samples showed no Tg, but only a large endothermic peak that was centered between 160 and 200 °C. The EPR analysis showed a broadening of the EPR resonance lines with increasing europium contents in the chitosan membranes due to the magnetic dipole–dipole coupling and spin–spin exchange between the Eu2+ ions. Moreover, the electrolytes based on chitosan and europium triflate presented good flexibility, homogeneity, and transparency.